Modelo de demanda de transporte urbano, caso práctico: Línea 4 del Metro-bus - González Vargas, Carlos Arturo; Jazmín Rodríguez, Luis Ángel; Pacheco Barreiro, Alejandro Alberto (My University, 2013)
Modelo de demanda de transporte urbano, caso práctico: Línea 4 del Metro-bus
Modelo de demanda de transporte urbano, caso práctico: Línea 4 del Metro-bus
Keywords: Modelo de demanda de transporte urbano, caso práctico: Línea 4 del Metro-bus